Morphological and biochemical characterization of pigment producing bacteria isolated from squid and Lala - Hanina Mohd Noor; Nabilah A.S.; Salina Mat Radzi; Maryam M.R. (American Institute of Physics Inc., 2024)
As the present trend throughout the world is shifting towards the use of ecofriendly and biodegradable commodities, there is an increasing need for natural pigments. However, the applications of natural pigments in human life are diverse and still in growing stages. Thus, attempt was made to isolate and identify pigment producing bacteria from squid and lala. In this study, four yellow-orange pigment producing bacteria, namely SO1, SO2, LO1 and LY1 were morphologically analyzed via Gram staining technique before being further identified and characterized using a series of biochemical test, including Indole, Methyl Red, Voges-Proskauer (VP), Catalase, Citrate, Nitrate Reductase, Urease, and Triple Sugar Iron (TSI). All four pigmented bacterial isolates were identified as Gram-negative with either bacillus or coccus shape. Three of the bacterial isolates produced orange pigment (SO1, SO2 and LO1) and showed positive result in Methyl Red (MR), Voges-Proskauer (VP), Catalase and Nitrate Reductase tests, while exhibited negative result in Indole, Citrate, Urease and Triple Sugar Iron (TSI) biochemical analysis. The other one yellow pigment bacterial isolate (LY1) was positive in three biochemical tests (MR, Catalase and Nitrate Reductase) and negative in five biochemical analysis (Indole, VP, Citrate, Urease and TSI). Each isolated pigment producing bacteria was also examined for their effect on growth parameters, including type of media (Nutrients agar, Luria-Bertani agar, Peptone-Glycerol agar), incubation temperature (30 C and 37 C) and incubation time (5 days and 7 days). Among three different types of agar media used, Luria-Bertani agar exhibited high bacterial growth and intense pigment production. Whilst, the optimum temperature and periods for pigment production was observed at 30 C and 5 days respectively. 2018 Author(s).